2021
DOI: 10.3389/fphar.2020.600175
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide Alleviates Hepatic Steatosis and Liver Injury in T2MD Rats via a GLP-1R Dependent AMPK Pathway

Abstract: Non-alcoholic fatty liver disease (NAFLD), ranging from non-alcoholic fatty liver to non-alcoholic steatohepatitis, can be prevalent in patients with type 2 diabetes mellitus (T2DM). However, no antidiabetic drug has been approved for the treatment of NAFLD in T2DM patients. Multiple daily injections of basal-bolus insulin are often the final therapeutic option for T2DM. We found that insulin treatment aggravated hepatic steatosis and oxidative stress in Zucker diabetic fatty (ZDF) rats. In addition to glycaem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 55 publications
3
17
0
Order By: Relevance
“…In the liver, GLP-1 stimulated the phosphorylation of AMPK and expression of Sirt1, then activated AMPK can phosphorylate ACC and reduce the production of malonyl-coA, thus up-regulating CPT1 expression, reducing FAT level, promoting fatty acid oxidation and reducing lipid deposition (Mottillo et al, 2016;Liu et al, 2015;Wan et al, 2021;O'Neill et al, 2013;Ben-Shlomo et al, 2011). Lira, as demonstrated in recent years, improves insulin resistance and hepatic lipid deposition in T2DM rats fed with a high-fat diet and promotes lipid degradation in liver and adipose tissues through activation of the AMPK pathway (He et al, 2016;He et al, 2020;Zhou et al, 2020). Similarly, our study demonstrated that PEG-Loxe, Lira, and Loxe notably upregulated the levels of Sirt1, p-AMPK, and p-ACC in the liver.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the liver, GLP-1 stimulated the phosphorylation of AMPK and expression of Sirt1, then activated AMPK can phosphorylate ACC and reduce the production of malonyl-coA, thus up-regulating CPT1 expression, reducing FAT level, promoting fatty acid oxidation and reducing lipid deposition (Mottillo et al, 2016;Liu et al, 2015;Wan et al, 2021;O'Neill et al, 2013;Ben-Shlomo et al, 2011). Lira, as demonstrated in recent years, improves insulin resistance and hepatic lipid deposition in T2DM rats fed with a high-fat diet and promotes lipid degradation in liver and adipose tissues through activation of the AMPK pathway (He et al, 2016;He et al, 2020;Zhou et al, 2020). Similarly, our study demonstrated that PEG-Loxe, Lira, and Loxe notably upregulated the levels of Sirt1, p-AMPK, and p-ACC in the liver.…”
Section: Discussionmentioning
confidence: 98%
“…Paraffin-embedded pancreatic tissues (4 μm thick) were dewaxed, hydrated, and sealed with 5% bovine serum albumin (BSA) solution for 30 min at room temperature. The samples were then incubated with anti-insulin or anti-GLP-1R overnight and horseradish peroxidase (HRP)-conjugated anti-rabbit secondary antibody for 30 min the following day, stained with stable diaminobenzidine (DAB) solution, re-stained with hematoxylin, dehydrated, blocked, and observed and imaged using an Olympus BX51 microscope (Tokyo, Japan) ( Zhou et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraperitoneal treatment of a synthetic peptide AWRK6, a candidate agonist of GLP-1 , can improve hepatic steatosis, glucose metabolism, and obesity in high energy diet (HED)-induced MAFLD mice, via modulating phosphoinositide 3-kinase ( PI3K )/Protein kinase B ( AKT )/AMP-activated protein kinase (AMPK) /acetyl-CoA carboxylase (ACC) signaling pathway [ 52 ]. In diabetic fatty rats, GLP-1 agonists liraglutide and Ex-4 can enhance the expression of PPARα through a GLP-1 receptor/ AMPK signaling pathway [ 53 ]. However, a cohort study showed that the treatment of GLP-1 agonist did not decrease the risk of NAFLD development compared to insulin treatment [ 54 ].…”
Section: Important Molecules and Their Mediated Signaling Pathways In Nafld And Nashmentioning
confidence: 99%
“…GLP-1/exendin-4 treatments have been associated with reduced oxidative stress. For example, antioxidant enzymes (SOD, glutathione reductase, CAT, and GPx), as well as glutathione levels, are improved, while other stress markers (lipid peroxidation and nonenzymatic glycosylated proteins) are reduced [ 95 , 131 ].…”
Section: Potential Role Of Pask and Exendin-4/glp-1 In Therapymentioning
confidence: 99%